HUBUNGAN PENGETAHUAN POLA ASUH DAN SANITASI LINGKUNGAN TERHADAP STATUS GIZI BALITA DIDESA TANJUNG GARBUS KAMPUNG - Sinaga, Haripin Togap (Jurnal Kesehatan Masyarakat Indonesia, 2024)
Background.  Child caring is an interaction between children and parents during parenting activities. The activities including educating, guiding and caring for children, taking care of food, drink, clothing, cleanliness, environment sanitation. This study aims to asess the relationship between parents knowledge and environmental sanitation on the nutritional status of children. Method. This research was carried out in the village of Tanjung Garbus, the village of Pagar Merbau District. This type of research is descriptive using a cross sectional design. Total sample is 45 families who have children. The data collected included parents knowledge, environmental sanitation, age, sex, weight and height of children. Data was collected by interview using a questionnaire. Nutritional status data was processed using the WHO Anthro application after which it was analyzed using the SPSS 20 application. Results. A total of 15.5% of respondents with poor knowledge had stunted children. There was a meaningful relationship between parents knowledge and stunting (p-value 0.002). A total of 13.4% of respondents with poor sanitation had stunted children. Statsitically showded that there was a relationship between poor sanitation and stunting (p-value of 0.010).  Parents need more information on environmental and nutritional education